Growth and Biomass Production of Tree Seedlings Irrigated at Varying Levels of Municipal Effluent in Indian Desert - Singh, G.; Bhati, M. (Indian Forester, 2013)
Scarcity of good quality water in arid areas has resulted in a search for an alternative source of water for biomass production and meeting the demand of fodder and wood. An experiment was conducted to see the growth of Eucalyptus camaldulensis, Acacia nilotica and Dalbergia sissoo using municipal effluent at Jodhpur, Rajasthan. Four treatments included T1 , municipal effluent at Â½ PET (Potential evapo-transpiration); T2 , municipal effluent at 1 PET; T3, municipal effluent at 2 PET; T4, canal water at 1 PET. Application of municipal effluent produced better height and collar 4 diameter in these seedlings. These variables were highest for E. camaldulrnsis than other two species. Percent increments in height and collar diameter were highest in 1998-99 in all these species except in D. sissoo, which indicated highest increment during 1999-00. However, the per cent growth increments decreased in later years, though it was relatively greater in T4 than in other treatments. Mean annual increment (MAI) in height, collar diameter and biomass was highest in E. camaldulensis and lowest in A. nilotica. MAI in T1 was at par to that in T4 , but it increased with increase in irrigation levels from Â½ PET to 2 PET. Relatively greater biomass in T1Â than in T4Â at 24 and 36 months of age was due to nutrients applied though municipal effluent. But at 48 months of age, lesser biomass in T1 than in T4 showed that municipal effluent application at 1/2 PET was not sufficient for the seedlings at 48 months onwards. The results suggest that recycling of municipal effluents through tree plantations can be an environmentally sustainable and reliable means for producing fuelwood, while restoring degraded land of dry areas.